A Survey on Clustering Routing Protocols Based on PSO in WSN - Enyan Sun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
LEACH is a traditional clustering routing protocol in wireless sensor network. When selecting the cluster head, LEACH does not consider sensor nodes’ energy and position information. It leads to uneven the distribution of cluster heads and uneven energy consumption of sensor nodes. Clustering routing protocols which are based on particle swarm optimization have been proposed to improve the performance of clustering routing protocols. This paper introduces and classifies the clustering routing protocols which are based on PSO and points the future direction.